2021
DOI: 10.1155/2021/7808070
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Nitrogen Content on the Corrosion Behavior of Powder Metallurgy Nickel‐Free Austenitic Stainless Steel

Abstract: Herein, powder metallurgy gas-solid nitriding was used to prepare a high-nitrogen Ni-free austenitic stainless steel with more than 1.0 wt.% N. Study of the microstructures and corrosion resistances of the as-prepared samples revealed that the corrosion weight loss, size, number of corrosion pits, and corrosion depth decreased as the N content increased from 1.19 to 1.37 wt.%. The self-corrosion current densities of the alloys were determined from their potentiodynamic polarization curves. The changes in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…The liquid phase should disappear in the later stage, making it difficult to shrink the pore and further improve the density. It can be seen from Figure 1 that the sintering pores have irregular shapes, which are completely different from some round type pores formed in alloys by high temperature solid phase sintering [ 37 , 38 ]. This is because the alloys are mainly composed of α-Fe phase grains, and the high density of powder metallurgical steel should be sintered at a temperature higher than 1120 °C [ 39 , 40 ].…”
Section: Results and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The liquid phase should disappear in the later stage, making it difficult to shrink the pore and further improve the density. It can be seen from Figure 1 that the sintering pores have irregular shapes, which are completely different from some round type pores formed in alloys by high temperature solid phase sintering [ 37 , 38 ]. This is because the alloys are mainly composed of α-Fe phase grains, and the high density of powder metallurgical steel should be sintered at a temperature higher than 1120 °C [ 39 , 40 ].…”
Section: Results and Analysismentioning
confidence: 99%
“…When the addition of Cu-Sn is 14 wt.%, the corrosion current density is only 4.30 × 10 −6 A/cm 2 . According to Faraday’s law, the higher corrosion current density of an alloy means a faster corrosion rate, and worse corrosion resistance [ 38 , 41 ]. With the increase in Cu-Sn content, the corrosion current density of the alloy decreases, indicating that the addition of Cu-Sn to Fe-Cu-Co can improve the corrosion resistance of the substrate.…”
Section: Results and Analysismentioning
confidence: 99%
“…The average FC value and wear rate from the experiments are shown in Fig- Comparing the presented results with the literature data, it can be concluded that the material obtained in this work has very promising corrosion resistance. Yu et al [26], investigating the effect of nitrogen content on the corrosion properties of stainless steel, showed that a higher nitrogen content improves corrosion resistance. In the material with the chemical composition Fe-17Cr-11Mn-3-Mo-1.2N (in wt.…”
Section: Tribology Testingmentioning
confidence: 99%
“…One of the techniques used to treat stainless steels is electropolishing [10][11][12][13][14] . This process is designed to change the surface properties of an object in order to improve its aesthetic value by smoothing and making the surface glossy and at the same time increasing its corrosion resistance 12,[15][16][17][18][19] . This method has many applications including food, automotive, and medical industries [20][21][22] .…”
mentioning
confidence: 99%